2019
DOI: 10.1021/acsomega.9b00369
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-Induced Emission-Active Hydrazide-Based Probe: Selective Sensing of Al3+, HF2, and Nitro Explosives

Abstract: ( E )- N ′-((2-Hydroxynaphthalen-1-yl)methylene)picolinohydrazide (H-PNAP) shows aggregation-induced emission (AIE) strictly in a 90% water/MeOH (v/v) mixture at 540 nm, and the solid-state emission is blue-shifted to 509 nm upon excitation at 400 nm. The AIE activity of H-PNAP is selectively quenched by 2,4,6-trinitrophenol (TNP) and 2,4-dinitrophenol (DNP) out of different nitroaromatic compounds with a limit of detection (LOD) of 7.79 × 10 –7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 123 publications
1
19
0
Order By: Relevance
“…The plot shows linearity upto 20 μM and accounts the static quenching and on above 20 μM of [Cu 2+ ] it shows an upward bend along with inclusion of dynamic process. The constancy of lifetime of the excited state fluorophore even on addition of Cu 2+ further confirms the static quenching [53,54] …”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…The plot shows linearity upto 20 μM and accounts the static quenching and on above 20 μM of [Cu 2+ ] it shows an upward bend along with inclusion of dynamic process. The constancy of lifetime of the excited state fluorophore even on addition of Cu 2+ further confirms the static quenching [53,54] …”
Section: Resultssupporting
confidence: 62%
“…The constancy of lifetime of the excited state fluorophore even on addition of Cu 2 + further confirms the static quenching. [53,54]…”
Section: Sensing Of Cu 2 +mentioning
confidence: 99%
“…To date, several studies have reported the successful application of ''ON-OFF''-type fluorescent sensors based on Schiff base derivatives, containing fluorophore units for the detection of Al 3+ ion only. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] On the other hand, a significant amount of research works have also been done on the development of efficient Zn 2+ ion sensors. [27][28][29][30] Furthermore, single chemical sensors that detect both Al 3+ and Zn 2+ ions in the same solvents are still few in number.…”
Section: Introductionmentioning
confidence: 99%
“…Several compounds in the reported literature were considering just a single wavelength either quenched or enhanced. To the best of the author’s knowledge, L2 is the first compound of its kind of simple conjugated thiophene-appended benzothiazole moiety for the ratiometric detection of metal ions. , Because ratiometric detection simultaneously measures the ratio of two emission bands, , it can exclude the distortion from the external environment and produce results that are more pronounced than intensity-based measurement.…”
Section: Introductionmentioning
confidence: 99%